Resin composition having improved haze and light transmittance and method for preparing same

The polycarbonate resin composition, featuring a matrix resin and crosslinked copolymer microspheres, addresses the challenge of balancing haze and light transmittance, achieving high energy efficiency and effective light diffusion in applications like lighting and displays.

JP7666943B2Active Publication Date: 2025-04-22CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021018607
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2015-04-10
Filing Date
2021-02-08
Publication Date
2025-04-22
Estimated Expiration
2036-04-11

AI Technical Summary

Technical Problem

Existing polycarbonate resin compositions struggle to achieve a balance between high haze and high light transmittance, leading to increased energy consumption and reduced efficiency in applications such as lighting and display materials.

Method used

A polycarbonate resin composition is developed, comprising a matrix resin and optionally crosslinked copolymer microspheres, which are alternating copolymers formed from olefin monomers and/or furans and their derivatives, along with monomers having anhydride, amide, and/or imide groups. These microspheres are homogeneously dispersed in the matrix resin, creating a transition layer that enhances light dispersion and maintains high transmittance.

Benefits of technology

The resin composition achieves a haze degree of 92% or more and a light transmittance of 55% or more, effectively reducing energy losses and conserving energy while maintaining excellent light diffusion properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007666943000001
    Figure 0007666943000001
  • Figure 0007666943000002
    Figure 0007666943000002
  • Figure 0007666943000003
    Figure 0007666943000003
Patent Text Reader

Abstract

To provide a resin composition having improved haze and light transmittance, and a process for preparing the same.SOLUTION: The resin composition is characterized by comprising the following blended components (a. matrix resin and b. optionally crosslinked copolymer microspheres), wherein the optionally crosslinked copolymer microspheres are alternating copolymers formed from olefin monomers and / or furan and its derivatives, and monomers having anhydride, amide and / or imide groups, optionally crosslinked with a crosslinking agent; preferably, the resin composition has a haze of 92% or more, and a light transmittance of 55% or more, preferably a haze of 92% or more, and a light transmittance of 59% or more, and more preferably a haze of 95% or more, and a light transmittance of 59% or more. The resin composition of the present invention can save a lot of energy while achieving excellent light diffusing effect, and at the same time reduces the material cost and can be easily industrially produced in mass.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the technical field of polymeric materials. The present invention further relates to a resin composition, particularly a polycarbonate resin composition having improved haze and light transmittance and a preparation method thereof, a material prepared by the resin composition, and a modifier for improving haze and light transmittance used in the material. [Background technology]

[0002] At present, due to the social energy shortage, the whole society is promoting energy conservation and environmental protection. In terms of lighting, in order to reduce energy consumption, China issued the "Notice on the Gradual Prohibition of (Sales of) Incandescent Lamps for Ordinary Lighting" in 2011. The notice stipulates that the import and sale of ordinary incandescent lamps for lighting of 100 watts or more will be banned nationwide. As a result, ordinary incandescent lamps will be gradually replaced by energy-saving lighting lamps in the future.

[0003] LED lamps have a very high energy conversion rate, low power consumption, long life, no heavy metals and other characteristics, so the use of LED lamps as energy-saving light sources has become a development trend, and traditional normal energy-saving lamps are gradually being replaced by LED lamps. However, because the light intensity per unit area of ​​LED lamps is too strong, people may experience dizziness, visual discomfort and other symptoms after looking directly at LED lamps. In addition, when LED and LCD are used as display materials, the same problems will be encountered again.

[0004] Therefore, when such a lamp that emits bright light is used as a light source or backlight, it is necessary to add an external material. When the light passes through this material, the diffusion effect of the material can convert the point light source into a surface light source and soften the light. This material is called a light diffusion material.

[0005] Light diffusing materials are mainly used in lighting such as lamps, luminous signs (especially backlit translucent signs), car skylights, and automobile lampshades. Light diffusing materials are also of great value in terms of building materials. Roofs and greenhouses made of translucent polycarbonate resin can prevent the adverse effects caused by direct sunlight. In terms of processing performance, plastics far exceed light diffusing glass, and are easy to process and transport. Such materials can also be used in displays and projection devices as scratch-resistant rear projection screens and thin laminates.

[0006] Polycarbonate resin is a very widely used engineering plastic, which has high light transmittance but low haze. Some polymethyl methacrylate microspheres, acrylate microspheres, or glass beads and other materials are generally used to increase the haze of the polycarbonate resin. However, the two materials have different refractive indices, so the light is refracted and absorbed many times on the surface of these particles. Therefore, the haze of the polycarbonate resin is greatly improved, and the damage caused by strong light to human eyes is also reduced, but at the same time, the transmittance of the light diffusion material is also significantly reduced, and finally only a small amount of energy is converted into light energy. As a result, energy consumption is high.

[0007] Chinese patent application CN101880450A discloses a method for preparing polycarbonate resin with high haze and high light transmittance. In this method, polymethyl methacrylate microbeads need to be added to polycarbonate to increase the haze of the polycarbonate resin. The polycarbonate resin can achieve a light transmittance of 80%, but at the same time, the haze is less than 30%.

[0008] Chinese patent application CN102250462A discloses a method for preparing a light-diffusing material using polycarbonate and using the light-diffusing material to manufacture an LED lampshade. In the above method, silicone resin and other light-diffusing agents are added to polycarbonate, so that the haze of the light-diffusing material reaches more than 90%, but the light transmittance is only 40%. Therefore, the light-diffusing material cannot be directly used as a light-diffusing material.

[0009] Therefore, how to prepare a material with high haze and high light transmittance has become an urgent problem.

[0010] [Disclosure] An object of the present invention is to provide a resin composition, particularly a polycarbonate resin composition, having improved haze and light transmittance, and it is preferable that the resin composition has high haze and high light transmittance.

[0011] Another object of the present invention is to provide a method for preparing the above-mentioned resin composition, which uses a general rubber plastic mixer to mix all the components to prepare the resin composition at once, thereby preparing a resin composition having high haze and high light transmittance. The above-mentioned method is easy to carry out.

[0012] According to the present invention, the above object is achieved by a polycarbonate resin composition having improved haze and light transmittance, the resin composition comprising the following mixed components (component a: matrix resin, component b: optionally crosslinked copolymer microspheres), the optionally crosslinked copolymer microspheres being an alternating copolymer formed from an olefin monomer and / or furan and its derivatives, and a monomer having an anhydride group, an amide group and / or an imide group, and optionally crosslinked with a crosslinking agent.

[0013] The matrix resin as the component a according to the present invention can be selected from at least one of transparent or translucent matrix resins, and is preferably selected from at least one of polycarbonate resin, acrylic resin, polyester resin, cyclic olefin polymer resin, polystyrene resin, poly(ethylene-co-1,4-cyclohexylene dimethylene terephthalate) (PETG), acrylonitrile-butadiene-styrene copolymer (ABS), acrylonitrile-styrene resin (AS), methyl methacrylate-butadiene-styrene copolymer (MBS), polypropylene, polyethylene, nylon, ethylene-vinyl acetate copolymer (EVA), allyl diglycol carbonate (CR-39), poly-4-methyl-1-pentene (TPX), poly(hydroxyethyl methacrylate) (HEMA), polyvinyl alcohol, cellulose acetate, cellulose nitrate, ethylene-tetrafluoroethylene copolymer, polyvinyl butyral, polyethersulfone, and derivatives thereof, and is preferably selected from polycarbonate resin, particularly aromatic polycarbonate resin.

[0014] The resin composition may further contain the following mixed component (c: silicone resin microspheres) as desired.

[0015] The resin composition, particularly the polycarbonate resin composition of the present invention, has the following fine structure (matrix resin as component a: continuous phase, optionally crosslinked copolymer microspheres as component b homogeneously dispersed in the matrix resin as the continuous phase, and optionally silicone resin microspheres as component c: dispersed phase), in which anhydride groups and other groups on the surface of the optionally crosslinked copolymer microspheres of component b can react with the matrix resin of the continuous phase, thereby forming a transition layer between the surface of the optionally crosslinked copolymer microspheres and the matrix resin, which transition layer contributes to the dispersion of the optionally crosslinked copolymer microspheres in the matrix resin. Furthermore, since the two kinds of microspheres of component b and optional component c in the dispersed phase and the matrix resin as the continuous phase have different refractive indices, when light passes through the composition, under the action of the microspheres (particularly under the combined action of the two kinds of microspheres), the original light source is dispersed very efficiently in the dispersed phase, and the point light source is converted into a surface light source, so that the haze degree of the matrix resin composition is significantly increased, and at the same time, the resin composition has a relatively high light transmittance.

[0016] The resin composition, particularly the polycarbonate resin composition of the present invention, has a haze of 92% or more, preferably a haze of 95% or more, and preferably at the same time has a light transmittance of 55% or more, preferably a light transmittance of 59% or more. In particular, the resin composition has a haze of 92% or more and a light transmittance of 55% or more, preferably a haze of 92% or more and a light transmittance of 59% or more, more preferably a haze of 95% or more and a light transmittance of 59% or more.

[0017] By using the above composition in practice, the energy loss can be effectively reduced and the goal of saving a lot of energy can be achieved.

[0018] In the above resin composition of the present invention, the polycarbonate resin as component a can be selected from various polycarbonate resins known in the art, preferably an aromatic polycarbonate, more preferably a copolycarbonate formed from a dihydric phenol and / or a phenol-modified diol. The polycarbonate resin can be prepared by a conventional method, preferably an interfacial polymerization method (i.e., a method in which a dihydric phenol, a phenol-modified diol with phosgene, and other carbonate precursors are reacted in a polymerization step). The dihydric phenol may be a compound of the following chemical formula (I):

[0019] [ka]

[0020] wherein R1 and R2 each represent an alkyl group having 1 to 6 carbon atoms, which may be linear, branched, or cyclic, and may be selected from methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, n-hexyl, isohexyl, cyclopentyl, cyclohexyl, and the like; a and b respectively represent the number of substituents R1 and R2 and are integers of 0 to 4; when R1 is 2 or more, the multiple R1s are the same or different from each other; when R2 is 2 or more, the multiple R2s are the same or different from each other; X is a single bond, an alkylene having 1 to 8 carbon atoms (e.g., methylene, ethylene, propylene, butylene, pentylene, hexylene, etc.), an alkylidene having 2 to 8 carbon atoms (e.g., ethylidene, isopropylidene, etc.), a cycloalkylene having 5 to 15 carbon atoms (e.g., cyclopentylene, cyclohexylene, etc.), a cycloalkylidene having 5 to 15 carbon atoms (e.g., cyclopentylidene, cyclohexylidene, etc.), -S-, -SO-, -O-, -CO-, or a structure represented by the following chemical formula (II-a) or chemical formula (II-b).

[0021]

change

[0022] The dihydric phenol of formula (I) may be any of various dihydric phenols for preparing polycarbonates, including 2,2-bis(4-hydroxyphenyl)propane [known as bisphenol A], bis(4-carboxyphenyl)methane, 1,1-bis(4-hydroxyphenyl)ethane, 2,2-bis(4-hydroxyphenyl)propane, 2,2-bis(4-hydroxyphenyl)butane, 2,2-bis(4-hydroxyphenyl)octane, 2,2-bis(4-hydroxyphenyl)phenylmethane, 2,2-bis(4-hydroxy-1-methylphenyl)methane ... bis(hydroxyaryl)alkanes such as 1,1-bis(4-hydroxyphenyl)propane, bis(4-hydroxyphenyl)naphthylmethane, 1,1-bis(4-hydroxy-tert-butylphenyl)propane, 2,2-bis(4-hydroxy-3-bromophenyl)propane, 2,2-bis(4-hydroxy-3,5-dimethylphenyl)propane, 2,2-bis(4-hydroxy-3-chlorophenyl)propane, 2,2-bis(4-hydroxy-3,5-dichlorophenyl)propane, and 2,2-bis(4-hydroxy-3,5-dibromophenyl)propane; -Bis(hydroxyaryl)cycloalkanes such as bis(4-hydroxyphenyl)cyclopentane, 1,1-bis(4-hydroxyphenyl)cyclohexane, and 1,1-bis(4-hydroxyphenyl)-3,5,5-trimethylcyclohexane; dihydroxy aromatic ethers such as 4,4'-dihydroxyphenyl ether and 4,4'-dihydroxy-3,3-dimethylphenyl ether; dihydroxydiaryl sulfides such as 4,4'-dihydroxydiphenyl sulfide and 4,4'-dihydroxy-3,3'-dimethyldiphenyl sulfide; Dihydroxydiaryl sulfoxides such as 4,4'-dihydroxydiphenyl sulfoxide and 4,4'-dihydroxy-3,3'-dimethyldiphenyl sulfoxide; dihydroxydiaryl sulfones such as 4,4'-dihydroxydiphenyl sulfone and 4,4'-dihydroxy-3,3'-dimethyldiphenyl sulfone; dihydroxybiphenyls such as 4,4'-dihydroxy-biphenyl; dihydroxydiphenylfluorenes such as 9,9-bis(4-hydroxyphenyl)fluorene and 9,9-bis(4-hydroxy-3-methylphenyl)fluorene;Dihydroxydiaryladamantanes such as 1,3-bis(4-hydroxyphenyl)adamantane, 2,2-bis(4-hydroxyphenyl)adamantane, and 1,3-bis(4-hydroxyphenyl)-5,7-dimethyladamantane; bis(4-hydroxyphenyl)diphenylmethane, 4,4'-[1,3-phenylenebis(1-methylethylidene)]bisphenol, 10,10-bis(4-hydroxyphenyl)-9-anthrone, 1,5-bis(4-hydroxyphenylthio)-2,3-dioxa-pentene, and α,ω-bishydroxyphenylpolydimethylsiloxane compounds are preferred, and 2,2-bis(4-hydroxyphenyl)propane, i.e., bisphenol A, is more preferred;

[0023] The phenol-modified diol used in the present invention may be a compound represented by the following chemical formula (III).

[0024] [ka]

[0025] In the formula, R3 and R4 each represent an alkyl group having 1 to 3 carbon atoms. Y represents a linear or branched alkylene having 2 to 15 carbon atoms; c and d represent the numbers of the substituents R3 and R4, respectively, and are integers of 0 to 4; n is an integer from 2 to 200, preferably an integer from 6 to 70; The alkyl of R3 and R4 may be selected from methyl, ethyl, n-propyl, and isopropyl, and when R3 is 2 or more, the multiple R3s are the same or different from each other, and when R4 is 2 or more, the multiple R4s are the same or different from each other; The straight or branched chain alkylene having 2 to 15 carbon atoms represented by Y may include alkylenes such as ethylene, propylene, butylene, isobutylene, pentylene, and isopentylene.

[0026] The phenol-modified diol is a compound derived from hydroxybenzoic acid or its alkyl ester, an acyl chloride, and a polyether-type diol. The hydroxybenzoic acid alkyl ester is preferably methyl hydroxybenzoate and ethyl hydroxybenzoate, the acyl chloride is preferably a compound obtained by reacting hydroxybenzoic acid with phosgene, and the polyether-type diol is preferably a compound represented by the chemical formula HO-(YO) n A compound having -H (where Y and n are defined in chemical formula (III)) is preferred, and polyethylene glycol, polypropylene glycol, and polybutylene glycol are preferred, with polybutylene glycol being more preferred.

[0027] The optionally crosslinked copolymer microspheres as component b in the resin composition of the present invention are alternating copolymers formed from olefin monomers and / or furan and derivatives thereof and monomers having an anhydride group, an amide group and / or an imide group, and are optionally crosslinked together with a crosslinking agent. The optionally crosslinked copolymer microspheres are preferably monodisperse copolymer microspheres. The optionally crosslinked copolymer microspheres may have a particle size of 0.01 to 20 microns, preferably 0.1 to 10 microns, more preferably 0.3 to 5 microns.

[0028] Said copolymer microspheres are preferably prepared by a self-stabilizing dispersion polymerization method, and can be prepared, for example, by the methods disclosed in Chinese Patent CN100579995C and Chinese Patent CN101781387B.

[0029] Specifically, for a monoolefin as an olefin monomer, for example, under nitrogen protection, a monomer and an initiator (and optionally a crosslinking agent) are added to a solvent to dissolve them, and reacted at 60°C to 90°C for 0.25 hours (15 minutes) to 12 hours to generate a dispersion system of alternating copolymer microspheres, which are then isolated by centrifugation to generate a white solid of the alternating copolymer. The mass concentration of the monomer in the reaction system is 1% to 50%, the initiator is an organic peroxide or an azo compound, and the mass concentration of the initiator in the reaction system is 0.01% to 1%. The solvent is an organic acid alkyl ester, a mixture of an aromatic hydrocarbon and an organic acid alkyl ester, or a mixture of an alkane and a ketone (the volume fraction of the ketone in the mixture of an alkane and a ketone is 5% to 65%).

[0030] For example, in the case of a conjugated diene as an olefin monomer, a monomer having an anhydride group, an amide group, and / or an imide group, and an initiator (and optionally a crosslinking agent) are added to a solvent under nitrogen protection to dissolve them thoroughly, and then the conjugated diene or a mixture thereof optionally having a crosslinking agent is added to the above solvent (reaction system) to dissolve it, and reacted at 50°C to 90°C for 0.5 hours (30 minutes) to 73 hours to generate a dispersion system of copolymer microspheres, which are then isolated by centrifugation and dried in vacuum to generate a white solid copolymer. In the above reaction, the initiator is an organic peroxide or an azo compound, the mass concentration of the initiator in the reaction system is 0.01 to 1%, and the above solvent is an organic acid alkyl ester, an aromatic hydrocarbon, or a mixture of an organic acid alkyl ester and an alkane (the volume fraction of the alkane in the above mixture of an organic acid alkyl ester and an alkane is 25% to 75%).

[0031] The content of the optionally crosslinked copolymer microspheres as component b may be 0.01 to 10 parts by weight, preferably 0.05 to 8 parts by weight, more preferably 0.1 to 5 parts by weight, and even more preferably 0.1 to 3 parts by weight, based on 100 parts by weight of the matrix resin as component a.

[0032] The monomer having an anhydride and / or imide group in the optionally crosslinked copolymer microspheres is preferably a compound having the following chemical formula (IV):

[0033] [ka]

[0034] In the formula, R5 represents an oxygen atom, an imino group or a derivative thereof, and is preferably an oxygen atom, an imino group, a phenylimino group, an alkylphenylimino group or an alkylimino group having 1 to 20 carbon atoms, and the alkyl group may be linear, branched or cyclic, and is more preferably an oxygen atom or an imino group.

[0035] The monomer having an anhydride group and / or an imide group may specifically be selected from at least one of maleic anhydride, maleimide, bismaleimide and phenylmaleimide.

[0036] The olefin monomer in the optionally crosslinked copolymer microspheres may be selected from one or more olefin monomers containing 2 to 30 carbon atoms, and more preferably is selected from one or more of butene (e.g., isobutene), butadiene (e.g., cis-butadiene), pentene, isoprene, cyclopentadiene, dicyclopentadiene, hexene, hexadiene, cyclohexene, cyclohexadiene, octene, octadiene, cyclooctadiene, styrene and its derivatives (e.g., hyperbranched styrene, sulfonated styrene, α-methylstyrene), and vinyl alkyl ethers.

[0037] The furan or derivative thereof in the optionally crosslinked copolymer microspheres is preferably selected from furan, furfural and its derivatives, 2,3-dihydrogenfuran and its derivatives, 2-methylfuran and its derivatives, 2-furancarboxylic acid and its derivatives, 2-furamide and its derivatives, furyl alcohol and its derivatives.

[0038] The optionally crosslinked copolymer microspheres may optionally include monomers having acid, ester, ether, and / or nitrile groups, which may be selected from one or more of vinyl acetate, acrylonitrile, vinyl alkyl ethers, and the like.

[0039] The method for preparing the optionally crosslinked copolymer microspheres may use a crosslinking agent, which may be an olefin-based organic compound having multiple functionality, such as an aliphatic divinyl ester, such as ethylene glycol dimethacrylate (EGDMA), ethylene glycol diacrylate, trimethylolpropane trimethacrylate (TMPTMA), and an aromatic divinylbenzene, and is preferably ethylene glycol dimethacrylate (EGDMA) and trimethylolpropane trimethacrylate (TMPTMA).

[0040] The content (molar ratio) of the monomer having an anhydride group, an amide group and / or an imide group contained in the optionally crosslinked copolymer microspheres may be 10% to 90%, preferably 20% to 80%, and more preferably 30% to 50%. The content (molar ratio) of one or more other monomers (olefin monomers and / or furan and derivatives thereof, and / or monomers having acid, ester, ether and / or nitrile groups) may be 10% to 90%, preferably 20% to 80%, and more preferably 30% to 50%. The content (molar ratio) of the crosslinking agent may be 0 to 50%, preferably 0 to 40%, and more preferably 0 to 30%.

[0041] The optionally crosslinked copolymer microspheres have a particle size distribution coefficient (U) of 1.05 to 1.0001, preferably 1.02 to 1.001, more preferably 1.017 to 1.001. The particle size distribution coefficient is determined by sampling from a polymer dispersion and observing the morphology of the polymer microspheres using a scanning electron microscope. The size of the microspheres is determined by the average particle diameter (D n ) and the particle size distribution is expressed by the dispersion coefficient. The formula is as follows:

[0042]

number

[0043] In the above formula, D i is the particle diameter i (nm), n is the volume of the sample, D w is the defined mathematical mean diameter.

[0044] The optionally crosslinked copolymer microspheres as component b may have a particle size of 0.01-20 microns, preferably 0.1-10 microns, more preferably 0.3-5 microns, which can be controlled by reaction process parameters such as reaction time, monomer concentration, and reaction medium.

[0045] The silicone resin in the silicone resin microspheres as optional component c in the resin composition of the present invention can be selected from various silicone resins known in the art, and is preferably an organopolysiloxane, the silicone resin containing at least one phosphonic acid group and / or phosphinic acid group and at least one nitrogen-containing organic group, and RPR 2 SiO 1 / 2 Units and / or RPRSiO 2 / 2 Units, and / or RPSiO 3 / 2 More preferably, the unit comprises at least one phosphonate or phosphinate moiety present in the unit, wherein the group "P" is an alkyl, cycloalkyl, alkenyl, alkynyl, or aryl group having 1 to 30 carbon atoms and containing a phosphonate or phosphinate substituent, and the group "R" is an alkyl, cycloalkyl, alkenyl, alkynyl, or aryl group having 1 to 30 carbon atoms, respectively.

[0046] The silicone resin microspheres as component c may have a particle size of 0.1 to 100 microns, preferably 1 to 50 microns, more preferably 2 to 30 microns, and even more preferably 2 to 12 microns.

[0047] The content of the silicone resin microspheres as component c is 0.01 to 10 parts by weight, preferably 0.05 to 8 parts by weight, more preferably 0.1 to 5 parts by weight, and even more preferably 0.1 to 2 parts by weight, relative to 100 parts by weight of the matrix resin as component a.

[0048] The resin composition of the present invention may contain at least one additive commonly used in plastics processing, the amount of which may be a common amount or may be adjusted according to actual needs.

[0049] The method for preparing the resin composition of the present invention includes a step of melt-mixing all the components including a matrix resin as component a, optionally crosslinked copolymer microspheres as component b, and optionally silicone resin microspheres as component c, at once using a general rubber plastic mixer and a general melt-mixing method in rubber plastic processing.

[0050] During the preparation, the mixing temperature of the above materials (all components) should be selected from the range that is the same as the general processing temperature of the matrix resin and ensures that the matrix resin is not decomposed but is completely melted. In addition, general additives in plastic processing may be added to the mixed materials in appropriate amounts according to the needs of the method. During the mixing, the various components including the matrix resin and optionally crosslinked copolymer microspheres, and optionally silicone resin microspheres, may be added simultaneously to a melt mixer via metering and other means for melt mixing. Alternatively, the various components may be premixed homogeneously in the same mixer, and then melt mixed and extruded at once using a rubber plastic mixer to obtain a resin composition.

[0051] The rubber plastic mixer used in the preparation method of the present invention can be an open mill, an internal mixer, a single screw extruder, a twin screw extruder or a torque rheometer, etc. The mass mixer is selected from high speed stirrers, kneaders and other mechanical mixers commonly used in the present technology.

[0052] The resin composition of the present invention is obtained by melt-mixing all components including a matrix resin and optionally crosslinked copolymer microspheres, optionally including silicone resin microspheres, at once. In the composition thus obtained, the optionally crosslinked copolymer microspheres and the optional silicone resin microspheres are homogeneously dispersed in the matrix resin as a continuous phase, and when both of the above two types of microspheres are included, both of the above two types of microspheres are in a monodispersed state. The above optionally crosslinked copolymer microspheres have anhydride groups and other groups on their crosslinked surfaces, and therefore undergo ester exchange with structures such as carbonyl groups on the molecular chains of the matrix resin (particularly polycarbonate resin), thereby further contributing to diffusion in the matrix resin. When light passes through the composition, the incident light is dispersed in the dispersed phase under the action of the microspheres (under the combined action of the above two types of microspheres), resulting in the point light source being converted into a surface light source, thereby significantly increasing the haze of the resin composition, and at the same time, the resin composition can have a relatively high light transmittance. As a result, a lot of energy can be saved. Meanwhile, the amount of material used is reduced, resulting in a significant reduction in material costs.

[0053] The present invention further provides a material having high haze and high light transmittance prepared from the resin composition of the present invention.The material is preferably a light diffusing material.The material can be used in lighting such as lamps, luminous signs, car skylights, and car lampshades, building materials such as roofs and greenhouses, displays and projection devices as scratch-resistant rear projection screens and thin laminates, and light diffusing plates for LCDs and LEDs.

[0054] The present invention further provides a modifier for improving haze and light transmittance, the modifier comprising the above-mentioned optionally crosslinked copolymer microspheres, and optionally comprising the above-mentioned silicone resin microspheres. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0055] The present invention will be further described below with reference to examples, although the scope of the present invention is not limited to these examples.

[0056] The experimental data in the examples are measured using the following instruments (and equipment) and measuring methods.

[0057] (1) Instruments for measuring experimental data: WGT-S transmittance and haze measuring instrument.

[0058] (2) Methods for measuring experimental data: China National Standard GB / T2410-2008.

[0059] Example 1 Polycarbonate resin (Bayer (Germany), product name: 2405) was placed in a hot air dryer and dried at 120°C for 4 hours, and then homogeneously mixed with silicone resin microspheres (Momentive, product name: TOSPEARL3120, particle size 12 microns), cross-linked copolymer microspheres [prepared according to the method disclosed in Chinese patent CN100579995C, particle size 0.1 microns, particle size diffusion coefficient 1.0002. In the above copolymer, the content (molar ratio) of styrene is 40%, the content (molar ratio) of maleimide is 40%, and the content (molar ratio) of divinylbenzene as a cross-linking agent is 20%], and antioxidant 1010. In the above mixing, 0.05 parts by weight of silicone resin microspheres, 5 parts by weight of cross-linked copolymer microspheres, and 0.1 parts by weight of antioxidant were used per 100 parts by weight of polycarbonate resin. Mixing was performed in a twin screw extruder, where the temperature in the feed zone was 200-240° C., the temperature in the mixing zone was 240-280° C., and the temperature in the mold was 200-240° C. After extrusion pelletization, the pellets were injection molded into standard test specimens. The test results are shown in Table 1.

[0060] Comparative Example 1 Polycarbonate resin (product name: 2405, manufactured by Bayer AG, Germany) was placed in a hot air dryer and dried at 120°C for 4 hours, and then mixed homogeneously with antioxidant 1010. In the above mixing, 0.1 parts by weight of antioxidant was used per 100 parts by weight of polycarbonate resin. Mixing was performed using a twin-screw extruder, in which the temperature of the feed section was 200-240°C, the temperature of the mixing section was 240-280°C, and the temperature of the mold was 200-240°C. After extrusion pelletization, the pellets were injection molded into standard test specimens. The test results are shown in Table 1.

[0061] Comparative Example 2 Polycarbonate resin (Bayer (Germany), product name: 2405) was placed in a hot air dryer and dried at 120°C for 4 hours, and then homogeneously mixed with silicone resin microspheres (Momentive, product name: TOSPEARL3120, particle size 12 microns) and antioxidant 1010. In the above mixing, 0.05 parts by weight of silicone resin microspheres and 0.1 parts by weight of antioxidant were used per 100 parts by weight of polycarbonate resin. Mixing was performed using a twin-screw extruder, in which the temperature of the feed section was 200-240°C, the temperature of the mixing section was 240-280°C, and the temperature of the mold was 200-240°C. After extrusion pelletization, the pellets were injection molded into standard test specimens. The test results are shown in Table 1.

[0062] [Example 1-b] Polycarbonate resin (Bayer (Germany), product name: 2405) was placed in a hot air dryer and dried at 120°C for 4 hours, and then crosslinked copolymer microspheres [prepared according to the method disclosed in Chinese patent CN100579995C. Particle size: 0.1 microns, particle size diffusion coefficient: 1.0002. In the copolymer, the styrene content (molar ratio) was 40%, the maleimide content (molar ratio) was 40%, and the crosslinking agent divinylbenzene content (molar ratio) was 20%] and 1010 antioxidants were mixed homogeneously. In the above mixing, 5 parts by weight of crosslinked copolymer microspheres and 0.1 parts by weight of antioxidant were used per 100 parts by weight of polycarbonate resin. Mixing was performed using a twin-screw extruder, in which the temperature of the feed section was 200-240°C, the temperature of the mixing section was 240-280°C, and the temperature of the mold was 200-240°C. After extrusion pelletization, the pellets were injection molded into standard specimens for testing. The test results are shown in Table 1.

[0063] Example 2 Polycarbonate resin (manufactured by Bayer (Germany), product name: ET3113) was dried in a hot air dryer at 120°C for 4 hours, and then homogeneously mixed with silicone resin microspheres (manufactured by Dow Corning, product name: 30-424, particle size 2 microns), cross-linked copolymer microspheres [prepared according to the method disclosed in Chinese Patent CN100579995C. Particle size 0.3 microns, particle size diffusion coefficient 1.017. In the above copolymer, the styrene content (molar ratio) is 65%, the maleimide content (molar ratio) is 33.5%, and the content (molar ratio) of EGDMA, which is a cross-linking agent, is 1.5%], and antioxidant 168. In the above mixing, 0.1 parts by weight of silicone resin microspheres, 3 parts by weight of cross-linked copolymer microspheres, and 0.1 parts by weight of antioxidant were used per 100 parts by weight of polycarbonate resin. Mixing was performed in a twin screw extruder, where the temperature in the feed zone was 200-240° C., the temperature in the mixing zone was 240-280° C., and the temperature in the mold was 200-240° C. After extrusion pelletization, the pellets were injection molded into standard test specimens. The test results are shown in Table 1.

[0064] Comparative Example 4 Polycarbonate resin (manufactured by Bayer (Germany), product name: ET3113) was placed in a hot air dryer, dried at 120°C for 4 hours, and then mixed homogeneously with antioxidant 168. In the above mixing, 0.1 parts by weight of antioxidant was used per 100 parts by weight of polycarbonate resin. Mixing was performed using a twin-screw extruder, in which the temperature of the feed section was 200-240°C, the temperature of the mixing section was 240-280°C, and the temperature of the mold was 200-240°C. After extrusion pelletization, the pellets were injection molded into standard test specimens. The test results are shown in Table 1.

[0065] Comparative Example 5 Polycarbonate resin (manufactured by Bayer (Germany), product name: ET3113) was placed in a hot air dryer and dried at 120°C for 4 hours, and then homogeneously mixed with silicone resin microspheres (manufactured by Dow Corning, product name: 30-424, particle size 2 microns) and antioxidant 168. In the above mixing, 0.1 parts by weight of silicone resin microspheres and 0.1 parts by weight of antioxidant were used per 100 parts by weight of polycarbonate resin. Mixing was performed using a twin-screw extruder, in which the temperature of the feed section was 200-240°C, the temperature of the mixing section was 240-280°C, and the temperature of the mold was 200-240°C. After extrusion pelletization, the pellets were injection molded into standard test specimens. The test results are shown in Table 1.

[0066] [Example 2-b] Polycarbonate resin (manufactured by Bayer (Germany), product name: ET3113) was placed in a hot air dryer and dried at 120°C for 4 hours, and then crosslinked copolymer microspheres [prepared according to the method disclosed in Chinese Patent CN100579995C. Particle size: 0.3 microns, particle size diffusion coefficient: 1.017. In the copolymer, the styrene content (molar ratio) was 65%, the maleimide content (molar ratio) was 33.5%, and the crosslinking agent EGDMA content (molar ratio) was 1.5%] and 168% antioxidant were mixed homogeneously. In the above mixing, 3 parts by weight of crosslinked copolymer microspheres and 0.1 parts by weight of antioxidant were used per 100 parts by weight of polycarbonate resin. Mixing was performed using a twin-screw extruder, in which the temperature of the feed section was 200-240°C, the temperature of the mixing section was 240-280°C, and the temperature of the mold was 200-240°C. After extrusion pelletization, the pellets were injection molded into standard specimens for testing. The test results are shown in Table 1.

[0067] Example 3 Polycarbonate resin (Bayer (Germany), product name: 3103) was placed in a hot air dryer and dried at 120°C for 6 hours, and then homogeneously mixed with silicone resin microspheres (Dow Corning, product name: 30-424, particle size 2 microns), cross-linked copolymer microspheres [prepared according to the method disclosed in Chinese patent CN100579995C, particle size 0.8 microns, particle size diffusion coefficient 1.039. In the copolymer, the content (molar ratio) of α-methylstyrene is 45%, the content (molar ratio) of maleic anhydride is 45%, and the content (molar ratio) of EGDMA as a cross-linking agent is 10%], and antioxidant B225. In the above mixing, 0.3 parts by weight of silicone resin microspheres, 1.5 parts by weight of cross-linked copolymer microspheres, and 0.1 parts by weight of antioxidant were used per 100 parts by weight of polycarbonate resin. Mixing was performed in a twin screw extruder, where the temperature in the feed zone was 200-240° C., the temperature in the mixing zone was 240-280° C., and the temperature in the mold was 200-240° C. After extrusion pelletization, the pellets were injection molded into standard test specimens. The test results are shown in Table 1.

[0068] Comparative Example 7 Polycarbonate resin (product name: 3103, manufactured by Bayer AG, Germany) was placed in a hot air dryer and dried at 120°C for 6 hours, and then mixed homogeneously with antioxidant B225. In the above mixing, 0.1 parts by weight of antioxidant was used per 100 parts by weight of polycarbonate resin. Mixing was performed using a twin-screw extruder, in which the temperature of the feed section was 200-240°C, the temperature of the mixing section was 240-280°C, and the temperature of the mold was 200-240°C. After extrusion pelletization, the pellets were injection molded into standard test specimens. The test results are shown in Table 1.

[0069] Comparative Example 8 Polycarbonate resin (Bayer (Germany), product name: 3103) was placed in a hot air dryer and dried at 120°C for 6 hours, and then mixed homogeneously with silicone resin microspheres (Dow Corning, product name: 30-424, particle size 2 microns) and antioxidant B225. In the above mixing, 0.3 parts by weight of silicone resin microspheres and 0.1 parts by weight of antioxidant were used per 100 parts by weight of polycarbonate resin. Mixing was performed using a twin-screw extruder, in which the temperature of the feed section was 200-240°C, the temperature of the mixing section was 240-280°C, and the temperature of the mold was 200-240°C. After extrusion pelletization, the pellets were injection molded into standard test specimens. The test results are shown in Table 1.

[0070] Example 3-b Polycarbonate resin (Bayer (Germany), product name: 3103) was placed in a hot air dryer and dried at 120°C for 6 hours, and then homogeneously mixed with crosslinked copolymer microspheres [prepared according to the method disclosed in Chinese patent CN100579995C, particle size 0.8 microns, particle size diffusion coefficient 1.039. In the copolymer, the content (molar ratio) of α-methylstyrene is 45%, the content (molar ratio) of maleic anhydride is 45%, and the content (molar ratio) of EGDMA as a crosslinking agent is 10%] and antioxidant B225. In the above mixing, 1.5 parts by weight of crosslinked copolymer microspheres and 0.1 parts by weight of antioxidant were used per 100 parts by weight of polycarbonate resin. Mixing was performed in a twin screw extruder, where the temperature in the feed zone was 200-240° C., the temperature in the mixing zone was 240-280° C., and the temperature in the mold was 200-240° C. After extrusion pelletization, the pellets were injection molded into standard test specimens. The test results are shown in Table 1.

[0071] Example 4 Polycarbonate resin (SABIC, product name: 9945A) was placed in a hot air dryer and dried at 100°C for 6 hours, and then homogeneously mixed with silicone resin microspheres (Dow Corning, product name: 30-424, particle size 2 microns), crosslinked copolymer microspheres [prepared according to the method disclosed in Chinese Patent CN100579995C. Particle size 1.2 microns, particle size diffusion coefficient 1.047. In the copolymer, the hexene content (molar ratio) is 40%, the maleimide content (molar ratio) is 40%, and the crosslinking agent TMPTMA content (molar ratio) is 20%], and antioxidant B225. In the above mixing, 0.4 parts by weight of silicone resin microspheres, 1 part by weight of crosslinked copolymer microspheres, and 0.1 parts by weight of antioxidant were used per 100 parts by weight of polycarbonate resin. Mixing was performed in a twin screw extruder, where the temperature in the feed zone was 200-240° C., the temperature in the mixing zone was 240-280° C., and the temperature in the mold was 200-240° C. After extrusion pelletization, the pellets were injection molded into standard test specimens. The test results are shown in Table 1.

[0072] Comparative Example 10 Polycarbonate resin (SABIC, product name: 9945A) was placed in a hot air dryer, dried at 120°C for 6 hours, and then mixed homogeneously with antioxidant B225. In the above mixing, 0.1 parts by weight of antioxidant was used per 100 parts by weight of polycarbonate resin. Mixing was performed using a twin-screw extruder, in which the temperature of the feed section was 200-240°C, the temperature of the mixing section was 240-280°C, and the temperature of the mold was 200-240°C. After extrusion pelletization, the pellets were injection molded into standard test specimens. The test results are shown in Table 1.

[0073] Comparative Example 11 Polycarbonate resin (SABIC, product name: 9945A) was placed in a hot air dryer and dried at 100°C for 6 hours, and then mixed homogeneously with silicone resin microspheres (Dow Corning, product name: 30-424, particle size 2 microns) and antioxidant B225. In the above mixing, 0.4 parts by weight of silicone resin microspheres and 0.1 parts by weight of antioxidant were used per 100 parts by weight of polycarbonate resin. Mixing was performed using a twin-screw extruder, in which the temperature of the feed section was 200-240°C, the temperature of the mixing section was 240-280°C, and the temperature of the mold was 200-240°C. After extrusion pelletization, the pellets were injection molded into standard test specimens. The test results are shown in Table 1.

[0074] Example 4-b Polycarbonate resin (SABIC, product name: 9945A) was placed in a hot air dryer and dried at 120°C for 6 hours, and then crosslinked copolymer microspheres [prepared according to the method disclosed in Chinese Patent CN100579995C. Particle size: 1.2 microns, particle size diffusion coefficient: 1.047. In the copolymer, the hexene content (molar ratio) was 40%, the maleimide content (molar ratio) was 40%, and the crosslinking agent TMPTMA content (molar ratio) was 20%] and antioxidant B225 were mixed homogeneously. In the above mixing, 1 part by weight of crosslinked copolymer microspheres and 0.1 part by weight of antioxidant were used per 100 parts by weight of polycarbonate resin. Mixing was performed using a twin-screw extruder, in which the temperature of the feed section was 200-240°C, the temperature of the mixing section was 240-280°C, and the temperature of the mold was 200-240°C. After extrusion pelletization, the pellets were injection molded into standard specimens for testing. The test results are shown in Table 1.

[0075] Example 5 Polycarbonate resin (Formosa Idemitsu, product name: IR2200) was placed in a hot air dryer and dried at 120°C for 4 hours, and then homogeneously mixed with silicone resin microspheres (Shin-Etsu Chemical, product name: KPM590, particle size 2 microns), cross-linked copolymer microspheres [prepared according to the method disclosed in Chinese Patent CN101781387B. Particle size 2 microns, particle size diffusion coefficient 1.003. In the above copolymer, the content (molar ratio) of isoprene is 55%, the content (molar ratio) of maleimide is 40%, and the content (molar ratio) of EGDMA, which is a cross-linking agent, is 5%], and antioxidant 1076. In the above mixing, 0.5 parts by weight of silicone resin microspheres, 1 part by weight of cross-linked copolymer microspheres, and 0.1 parts by weight of antioxidant were used per 100 parts by weight of polycarbonate resin. Mixing was performed in a twin screw extruder, where the temperature in the feed zone was 200-240° C., the temperature in the mixing zone was 240-280° C., and the temperature in the mold was 200-240° C. After extrusion pelletization, the pellets were injection molded into standard test specimens. The test results are shown in Table 1.

[0076] Comparative Example 13 Polycarbonate resin (manufactured by Formosa Idemitsu, product name: IR2200) was placed in a hot air dryer, dried at 120°C for 4 hours, and then mixed homogeneously with antioxidant 1076. In the above mixing, 0.1 parts by weight of antioxidant was used per 100 parts by weight of polycarbonate resin. Mixing was performed using a twin-screw extruder, in which the temperature of the feed section was 200-240°C, the temperature of the mixing section was 240-280°C, and the temperature of the mold was 200-240°C. After extrusion pelletization, the pellets were injection molded into standard test specimens. The test results are shown in Table 1.

[0077] Comparative Example 14 Polycarbonate resin (manufactured by Formosa Idemitsu, product name: IR2200) was placed in a hot air dryer and dried at 120°C for 4 hours, and then homogeneously mixed with silicone resin microspheres (manufactured by Shin-Etsu Chemical Co., Ltd., product name: KPM590, particle size 2 microns) and antioxidant 1076. In the above mixing, 0.5 parts by weight of silicone resin microspheres and 0.1 parts by weight of antioxidant were used per 100 parts by weight of polycarbonate resin. Mixing was performed using a twin-screw extruder, in which the temperature of the feed section was 200-240°C, the temperature of the mixing section was 240-280°C, and the temperature of the mold was 200-240°C. After extrusion pelletization, the pellets were injection molded into standard test specimens. The test results are shown in Table 1.

[0078] [Example 5-b] Polycarbonate resin (manufactured by Formosa Idemitsu, product name: IR2200) was placed in a hot air dryer and dried at 120°C for 4 hours, and then crosslinked copolymer microspheres [prepared according to the method disclosed in Chinese Patent CN101781387B. Particle size: 2 microns, particle size diffusion coefficient: 1.003. In the copolymer, the content (molar ratio) of isoprene is 55%, the content (molar ratio) of maleimide is 40%, and the content (molar ratio) of EGDMA, which is a crosslinking agent, is 5%] and antioxidant 1076 were mixed homogeneously. In the above mixing, 1 part by weight of crosslinked copolymer microspheres and 0.1 part by weight of antioxidant were used per 100 parts by weight of polycarbonate resin. Mixing was performed using a twin-screw extruder, in which the temperature of the feed section was 200-240°C, the temperature of the mixing section was 240-280°C, and the temperature of the mold was 200-240°C. After extrusion pelletization, the pellets were injection molded into standard specimens for testing. The test results are shown in Table 1.

[0079] Example 6 Polycarbonate resin (Dow, product name: 201-22) was placed in a hot air dryer and dried at 120°C for 4 hours, and then homogeneously mixed with silicone resin microspheres (Momentive, product name: TOSPEARL145, particle size 4.5 microns), copolymer microspheres [prepared according to the method disclosed in Chinese Patent CN101781387B. Particle size 4 microns, particle size diffusion coefficient 1.009. In the copolymer, the butadiene content (molar ratio) is 70%, and the maleic anhydride content (molar ratio) is 30%], and antioxidant B225. In the above mixing, 5 parts by weight of silicone resin microspheres, 0.5 parts by weight of copolymer microspheres, and 0.1 parts by weight of antioxidant were used per 100 parts by weight of polycarbonate resin. Mixing was performed in a twin screw extruder, where the temperature in the feed zone was 200-240° C., the temperature in the mixing zone was 240-280° C., and the temperature in the mold was 200-240° C. After extrusion pelletization, the pellets were injection molded into standard test specimens. The test results are shown in Table 1.

[0080] Comparative Example 16 Polycarbonate resin (Dow, product name: 201-22) was placed in a hot air dryer, dried at 120°C for 4 hours, and then mixed homogeneously with antioxidant B225. In the above mixing, 0.1 parts by weight of antioxidant was used per 100 parts by weight of polycarbonate resin. Mixing was performed using a twin-screw extruder, in which the temperature of the feed section was 200-240°C, the temperature of the mixing section was 240-280°C, and the temperature of the mold was 200-240°C. After extrusion pelletization, the pellets were injection molded into standard test specimens. The test results are shown in Table 1.

[0081] Comparative Example 17 Polycarbonate resin (Dow, product name: 201-22) was placed in a hot air dryer and dried at 120°C for 4 hours, and then homogeneously mixed with silicone resin microspheres (Momentive, product name: TOSPEARL145, particle size 4.5 microns) and antioxidant B225. In the above mixing, 5 parts by weight of silicone resin microspheres and 0.1 parts by weight of antioxidant were used per 100 parts by weight of polycarbonate resin. Mixing was performed using a twin-screw extruder, in which the temperature of the feed section was 200-240°C, the temperature of the mixing section was 240-280°C, and the temperature of the mold was 200-240°C. After extrusion pelletization, the pellets were injection molded into standard test specimens. The test results are shown in Table 1.

[0082] [Example 6-b] Polycarbonate resin (Dow, product name: 201-22) was placed in a hot air dryer and dried at 120°C for 4 hours, and then prepared according to the method disclosed in Chinese patent CN101781387B. Particle size: 4 microns, particle size diffusion coefficient: 1.009. In the copolymer, the butadiene content (molar ratio) was 70%, and the maleic anhydride content (molar ratio) was 30%], and the antioxidant B225 were mixed homogeneously. In the mixing, 0.5 parts by weight of copolymer microspheres and 0.1 parts by weight of antioxidant were used per 100 parts by weight of polycarbonate resin. Mixing was performed using a twin-screw extruder, in which the temperature of the feed section was 200-240°C, the temperature of the mixing section was 240-280°C, and the temperature of the mold was 200-240°C. After extrusion pelletization, the pellets were injection molded into standard test specimens. The test results are shown in Table 1.

[0083] Example 7 Polycarbonate resin (Idemitsu Kosan Co., Ltd. (Japan), product name: LC1500) was placed in a hot air dryer and dried at 120°C for 4 hours, and then homogeneously mixed with silicone resin microspheres (Momentive Co., Ltd., product name: TOSPEARL105, particle size 0.5 microns), cross-linked copolymer microspheres [prepared according to the method disclosed in Chinese Patent CN100579995C, particle size 8 microns, particle size diffusion coefficient 1.015. In the above copolymer, the content (molar ratio) of butene is 35%, the content (molar ratio) of phenylmaleimide is 35%, and the content (molar ratio) of TMPTMA as a cross-linking agent is 30%], and antioxidant 126. In the above mixing, 10 parts by weight of silicone resin microspheres, 0.1 parts by weight of cross-linked copolymer microspheres, and 0.1 parts by weight of antioxidant were used per 100 parts by weight of polycarbonate resin. Mixing was performed in a twin screw extruder, where the temperature in the feed zone was 200-240° C., the temperature in the mixing zone was 240-280° C., and the temperature in the mold was 200-240° C. After extrusion pelletization, the pellets were injection molded into standard test specimens. The test results are shown in Table 1.

[0084] Comparative Example 19 Polycarbonate resin (Idemitsu Kosan Co., Ltd. (Japan), product name: LC1500) was placed in a hot air dryer, dried at 120°C for 4 hours, and then mixed homogeneously with antioxidant 126. In the above mixing, 0.1 parts by weight of antioxidant was used per 100 parts by weight of polycarbonate resin. Mixing was performed using a twin-screw extruder, in which the temperature of the feed section was 200-240°C, the temperature of the mixing section was 240-280°C, and the temperature of the mold was 200-240°C. After extrusion pelletization, the pellets were injection molded into standard test specimens. The test results are shown in Table 1.

[0085] Comparative Example 20 Polycarbonate resin (Idemitsu Kosan Co., Ltd. (Japan), product name: LC1500) was placed in a hot air dryer and dried at 120°C for 4 hours, and then homogeneously mixed with silicone resin microspheres (Momentive Co., Ltd., product name: TOSPEARL105, particle size 0.5 microns) and antioxidant 126. In the above mixing, 10 parts by weight of silicone resin microspheres and 0.1 parts by weight of antioxidant were used per 100 parts by weight of polycarbonate resin. Mixing was performed using a twin-screw extruder, in which the temperature of the feed section was 200-240°C, the temperature of the mixing section was 240-280°C, and the temperature of the mold was 200-240°C. After extrusion pelletization, the pellets were injection molded into standard test specimens. The test results are shown in Table 1.

[0086] Example 7-b Polycarbonate resin (Idemitsu Kosan Co., Ltd. (Japan), product name: LC1500) was placed in a hot air dryer and dried at 120°C for 4 hours, and then homogeneously mixed with crosslinked copolymer microspheres [prepared according to the method disclosed in Chinese patent CN100579995C, particle size 8 microns, particle size diffusion coefficient 1.015. In the copolymer, the butene content (molar ratio) is 35%, the phenylmaleimide content (molar ratio) is 35%, and the crosslinking agent TMPTMA content (molar ratio) is 30%] and antioxidant 126. In the above mixing, 0.1 parts by weight of crosslinked copolymer microspheres and 0.1 parts by weight of antioxidant were used per 100 parts by weight of polycarbonate resin. Mixing was performed in a twin screw extruder, where the temperature in the feed zone was 200-240° C., the temperature in the mixing zone was 240-280° C., and the temperature in the mold was 200-240° C. After extrusion pelletization, the pellets were injection molded into standard test specimens. The test results are shown in Table 1.

[0087] [Table 1]

[0088] As can be seen from the data in Table 1, compared with the sample pieces prepared from the resin composition without the addition of microspheres, the sample pieces with only the addition of silicone resin microspheres had a clear increase in haze, but a large decrease in light transmittance. In addition, the sample pieces with only the arbitrarily crosslinked copolymer microspheres described in the present invention could increase light transmittance and haze to a certain extent. By adding the above two types of microspheres, the haze increased obviously, and the light transmittance decreased, although not significantly. In the sample pieces with the above two types of microspheres, a haze of 95% or more was obtained, and a light transmittance of 59% or more was also obtained. Similarly, the polycarbonate sample of the present invention in which the above two types of microspheres are mixed has a high haze and a high light transmittance at the same time. The resin composition of the present invention can achieve an excellent light diffusion effect while saving a lot of energy, while at the same time reducing material costs, and can be easily industrially produced.

Claims

1. A resin composition having improved haze and light transmittance, the resin composition comprising a mixture of components (component a: matrix resin, component b: crosslinked copolymer microspheres crosslinked with a crosslinking agent, component c: silicone resin microspheres); The crosslinked copolymer microspheres are alternating copolymers formed from olefin monomers and monomers having anhydride and / or imide groups; The matrix resin as component a is a polycarbonate resin, the monomer having an anhydride group and / or an imide group is selected from at least one of maleic anhydride, maleimide, bismaleimide and phenylmaleimide; the olefin monomer is at least one olefin monomer containing from 2 to 30 carbon atoms; A resin composition, wherein the crosslinked copolymer microspheres are copolymer microspheres prepared by a self-stabilizing dispersion polymerization method.

2. 2. The resin composition according to claim 1, wherein the crosslinked copolymer microspheres are monodisperse copolymer microspheres.

3. 3. The resin composition according to claim 1, wherein the crosslinked copolymer microspheres have a particle size of 0.01 to 20 microns, and the particle size distribution coefficient is 1.05 to 1.0001.

4. The resin composition according to claim 3, wherein the crosslinked copolymer microspheres have a particle size of 0.1 to 10 microns.

5. The resin composition according to claim 3, wherein the crosslinked copolymer microspheres have a particle size of 0.3 to 5 microns.

6. The resin composition according to claim 3, wherein the crosslinked copolymer microspheres have a particle size distribution coefficient of 1.02 to 1.

001.

7. The resin composition according to claim 3, wherein the crosslinked copolymer microspheres have a particle size distribution coefficient of 1.017 to 1.

001.

8. The resin composition according to any one of claims 1 to 7, wherein the content of the crosslinked copolymer microspheres as component b is 0.01 to 10 parts by weight based on 100 parts by weight of the matrix resin as component a.

9. The resin composition according to claim 8, wherein the content of the crosslinked copolymer microspheres as component b is 0.05 to 8 parts by weight based on 100 parts by weight of the matrix resin as component a.

10. The resin composition according to claim 8, wherein the content of the crosslinked copolymer microspheres as component b is 0.1 to 5 parts by weight based on 100 parts by weight of the matrix resin as component a.

11. The resin composition according to claim 1, wherein the polycarbonate resin is an aromatic polycarbonate resin.

12. The resin composition according to claim 1, wherein the olefin monomer is at least one of butene, butadiene, pentene, isoprene, cyclopentadiene, dicyclopentadiene, hexene, hexadiene, cyclohexene, cyclohexadiene, octene, octadiene, cyclooctadiene, styrene, sulfonated styrene, α-methylstyrene, and vinyl alkyl ether.

13. The resin composition according to claim 12, wherein the butene is isobutene.

14. The resin composition according to claim 12, wherein the butadiene is cis-butadiene.

15. The resin composition according to any one of claims 1 to 14, wherein the copolymer further comprises a monomer having an acid, ester, ether and / or nitrile group.

16. 16. The resin composition according to claim 15, wherein the monomer having an acid, ester, ether and / or nitrile group is selected from at least one of vinyl acetate, acrylonitrile, and vinyl alkyl ether.

17. The resin composition according to any one of claims 1 to 16, characterized in that the content of the monomer having an anhydride group and / or an imide group contained in the crosslinked copolymer microspheres is 10 to 90 mol %, the total content of the other one or more monomers is 10 to 90 mol %, and the content of the crosslinking agent is more than 0 mol % and not more than 50 mol %.

18. The resin composition according to claim 17, wherein the content of the monomer having an anhydride group and / or an imide group contained in the crosslinked copolymer microspheres is 20-80 mol %, and the total content of the other one or more monomers is 20-80 mol %.

19. The resin composition according to claim 17, wherein the content of the monomer having an anhydride group and / or an imide group contained in the crosslinked copolymer microspheres is 30-50 mol %, and the total content of the other one or more monomers is 30-50 mol %.

20. 18. The resin composition according to claim 17, wherein the content of the crosslinking agent contained in the crosslinked copolymer microspheres is more than 0 mol % and is not more than 40 mol %.

21. 18. The resin composition according to claim 17, wherein the content of the crosslinking agent contained in the crosslinked copolymer microspheres is more than 0 mol % and is not more than 30 mol %.

22. The resin composition according to any one of claims 1 to 21, characterized in that the crosslinking agent is selected from polyfunctional olefin-based organic compounds.

23. 23. The resin composition according to claim 22, wherein the crosslinking agent is selected from the group consisting of divinylbenzene, ethylene glycol dimethacrylate, and trimethylolpropane trimethacrylate.

24. 2. The resin composition according to claim 1, wherein the content of the silicone resin microspheres as component c is 0.01 to 10 parts by weight based on 100 parts by weight of the matrix resin as component a.

25. The resin composition according to claim 24, wherein the content of the silicone resin microspheres as component c is 0.05 to 8 parts by weight based on 100 parts by weight of the matrix resin as component a.

26. The resin composition according to claim 24, wherein the content of the silicone resin microspheres as component c is 0.1 to 5 parts by weight based on 100 parts by weight of the matrix resin as component a.

27. 2. The resin composition according to claim 1, wherein the silicone resin microspheres have a particle size of 0.1 to 100 microns.

28. The resin composition according to claim 27, wherein the silicone resin microspheres have a particle size of 1 to 50 microns.

29. The resin composition according to claim 27, wherein the silicone resin microspheres have a particle size of 2 to 30 microns.

30. 2. The resin composition according to claim 1, wherein the silicone resin in the silicone resin microspheres is an organopolysiloxane.

31. 31. The resin composition according to claim 30, wherein the silicone resin comprises at least one phosphonic acid group and / or phosphinic acid group, and at least one nitrogen-containing organic group.

32. The resin composition according to any one of claims 1 to 31, characterized in that the resin composition has a haze of 92% or more.

33. The resin composition according to claim 32, characterized in that the resin composition has a haze of 95% or more.

34. The resin composition according to claim 32 or 33, characterized in that the resin composition also has a light transmittance of 55% or more.

35. The resin composition according to claim 32 or 33, characterized in that the resin composition also has a light transmittance of 59% or more.

36. A method for preparing a resin composition according to any one of claims 1 to 35, comprising melt-mixing all components of the resin composition at once using a rubber plastic mixer; A method of preparing the crosslinked copolymer microspheres further comprising: For monoolefin as olefin monomer, add monomer, initiator and crosslinker to a solvent under nitrogen protection to dissolve them, and react at 60°C to 90°C for 0.25 hours to 12 hours to generate a dispersion of alternating copolymer microspheres, and then isolate by centrifugation to generate a white solid of the alternating copolymer; for said monoolefin, the mass concentration of monomer in said reaction system is 1%-50%, the initiator is an organic peroxide or an azo compound, the mass concentration of initiator in said reaction system is 0.01%-1%, said solvent is an organic acid alkyl ester, a mixture of an aromatic hydrocarbon and an organic acid alkyl ester, or a mixture of an alkane and a ketone, the volume fraction of ketone in said mixture of an alkane and a ketone is 5%-65%, For conjugated diene as olefin monomer, add monomer having anhydride group, amide group and / or imide group, initiator and crosslinking agent to a solvent under nitrogen protection to dissolve them thoroughly, then add the mixture of conjugated diene or crosslinking agent to the above solvent to dissolve, react at 50°C to 90°C for 0.5 hours to 73 hours to generate a dispersion of copolymer microspheres, then isolate by centrifugation and dry in vacuum to generate a white solid of copolymer; In the above reaction of the conjugated diene, the initiator is an organic peroxide or an azo compound, the mass concentration of the initiator in the reaction system is 0.01 to 1%, the solvent is an organic acid alkyl ester, an aromatic hydrocarbon, or a mixed solution of an organic acid alkyl ester and an alkane, and the volume fraction of the alkane in the mixed solution of an organic acid alkyl ester and an alkane is 25% to 75%.

37. A material having improved haze and light transmittance prepared from the resin composition according to any one of claims 1 to 35.

38. 38. The material of claim 37, wherein the material is a light diffusing material.

39. 38. The material according to claim 37, characterized in that it is used in lighting, building materials, displays and projection devices as scratch-resistant rear projection screens and thin laminates, and light diffusion plates for LCD and LED.

40. 40. The material according to claim 39, characterized in that the material is used in lamps, luminous signs, car skylights, automotive lampshades, roofs or greenhouses.

41. A modifier for improving haze and light transmittance, further comprising crosslinked copolymer microspheres as defined in any one of claims 1 to 23, and silicone resin microspheres as defined in any one of claims 24 to 31.

Citation Information

Patent Citations

  • Light-diffusive polycarbonate-based resin composition, and light-diffusive plate using the same

    JP2007016079A

  • Light diffusion sheet and backlight unit

    JP2010044146A

  • JPP7268952B

  • Light-diffusible resin composition

    WO2013141005A1

  • DC power grid and equipment

    WO2016077813A1